2021
DOI: 10.1002/acr.24420
|View full text |Cite
|
Sign up to set email alerts
|

How Foot Progression Angle Affects Knee Adduction Moment and Angular Impulse in Patients With and Without Medial Knee Osteoarthritis: A Meta‐Analysis

Abstract: Objective. To investigate effects of foot progression angle (FPA) modification on the first and second peaks of external knee adduction moment (EKAM) and knee adduction angular impulse (KAAI) in individuals with and without medial knee osteoarthritis (OA) during level walking.Methods. PubMed, Embase, the Cumulative Index to Nursing and Allied Health Literature (CINAHL), Web of Science, and SPORTDiscus were searched from inception to February 2020 by 2 independent reviewers. Included studies compared FPA modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Toe-in reduced KAM1 (medium effect) but increased KAM2 (small effect). Our findings support three previous systematic reviews [ 13 15 ]. Simic et al in 2011 suggested that trunk lean consistently reduced KAM1 and toe-out consistently reduced KAM2 [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…Toe-in reduced KAM1 (medium effect) but increased KAM2 (small effect). Our findings support three previous systematic reviews [ 13 15 ]. Simic et al in 2011 suggested that trunk lean consistently reduced KAM1 and toe-out consistently reduced KAM2 [ 13 ].…”
Section: Discussionsupporting
confidence: 93%
“…A systematic review found that in healthy individuals, both toein and toe-out gait reduced KAM and KAM angular impulse compared to natural gait, while in individuals with knee OA, only toe-out gait appeared to reduce these gait parameters 81 . Using standing MRI, a small amount of lateralization of contact for both toe-out and toe-in postures in individuals with mild knee OA was found 82 , indicating accurate analyses of joint kinematics during gait may be needed to reveal more subtle changes.…”
Section: Biomechanics In Oa Treatmentmentioning
confidence: 99%
“…Given knee loading can be redistributed from medial to lateral compartment of the knee joint, gait retraining has been suggested to lower medial knee loading, and modification of foot progression angle is a commonly adopted strategy [ 8 , 9 ]. It has been reported that individuals with medial knee OA may report an improvement in knee symptoms following a six-week gait retraining to lower medial knee loading by toe-in gait [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, its clinical efficacy has yet been examined. Additionally, the effectiveness of gait retraining on patients with early-stage knee OA is insufficient [ 9 ].…”
Section: Introductionmentioning
confidence: 99%